The growth of discs and bulges during hierarchical galaxy formation – II. Metallicity, stellar populations and dynamical evolution. Issue 4 (29th November 2016) - Tonini, C.; Mutch, S. J.; Wyithe, J. S. B.; Croton, D. J.
Abstract: We investigate the properties of the stellar populations of model galaxies as a function of galaxy evolutionary history and angular momentum content. We use the new semi-analytic model presented in Tonini et al. This new model follows the angular momentum evolution of gas and stars, providing the base for a new star formation recipe, and treatment of the effects of mergers that depends on the central galaxy dynamical structure. We find that the new recipes have the effect of boosting the efficiency of the baryonic cycle in producing and recycling metals, as well as preventing minor mergers from diluting the metallicity of bulges and ellipticals. The model reproduces the stellar mass–stellar metallicity relation for galaxies above 10 10 solar masses, including Brightest Cluster Galaxies. Model discs, galaxies dominated by instability-driven components, and merger-driven objects each stem from different evolutionary channels. These model galaxies therefore occupy different loci in the galaxy mass–size relation, which we find to be in accord with the ATLAS 3D classification of disc galaxies, fast rotators and slow rotators. We find that the stellar populations' properties depend on the galaxy evolutionary type, with more evolved stellar populations being part of systems that have lost or dissipated more angular momentum during their assembly history.